2002
DOI: 10.1162/108819802766269557
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Voluntary Industry Standards in Environmental Supply‐Chain Management

Abstract: Summary Our article uses a new institutional economics (NIE) framework to explore the role of voluntary industry standards in the development and implementation of environmental supplier‐management programs in the computer industry. We examine two different voluntary standards, one for the management of design for environment (DfE) in the semiconductor fabrication equipment sector and the other for assessing the implementation and use of environmental management systems throughout the computer industry supply … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Conversely, a lack of standards implies higher transaction costs associated with the procurement of sustainably produced goods. These costs include research and development costs for establishing product sustainability specifications, resources spent for supplier ‘search’ and ‘qualification’ efforts on a custom basis, as well as investments to develop the suppliers’ production volumes and to monitor compliance with sustainability requirements (Rosen et al ., ; Kogg, ; Pagell et al ., ). In such a situation of increased asset‐specificity, the development of collaborative approaches becomes the economically rational choice of interorganizational relationship management to ensure the availability of sustainably produced supply and decrease the risk of suppliers’ opportunistic behavior (Pagell et al ., ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, a lack of standards implies higher transaction costs associated with the procurement of sustainably produced goods. These costs include research and development costs for establishing product sustainability specifications, resources spent for supplier ‘search’ and ‘qualification’ efforts on a custom basis, as well as investments to develop the suppliers’ production volumes and to monitor compliance with sustainability requirements (Rosen et al ., ; Kogg, ; Pagell et al ., ). In such a situation of increased asset‐specificity, the development of collaborative approaches becomes the economically rational choice of interorganizational relationship management to ensure the availability of sustainably produced supply and decrease the risk of suppliers’ opportunistic behavior (Pagell et al ., ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, Rosen et al . (, p. 113) have demonstrated that sustainability standards 'help firms reduce transaction costs by legitimizing, simplifying, and routinizing the incorporation of environmental elements into supplier management'. Hatanaka et al .…”
Section: Literature Reviewmentioning
confidence: 99%
“…This suggests that most MNCs may be, at worst, harmonizing up to their OECD-based home country environmental standards, rather than opting for lax standards. These findings undoubtedly reflect the growing pressures MNCs face from their customers in the developed world , from their investors (Dasgupta et al 1998;Hamilton 1995), from multicountry environmental directives (Rosen et al 2002) and treaties (Montreal Protocol), and from their neighbors Konar and Cohen 1997) to improve their environmental performance and the environmental performance of their suppliers (Rosen et al 2002, 108).…”
Section: Globalization Firm-based Standards and Environmental Supplmentioning
confidence: 99%
“…The extended producer responsibility (EPR) principle plays a similar role. The purpose is to promote life cycle environmental improvements, to reduce pollution as well as resource and energy use, by extending the responsibility of the producer to other parts of the life cycle, especially the product's end-of-life (EOL) phase (Honkasalo 2001, Rosen et al 2002, Sanne 2002, Li and Geiser 2005, Gehin et al 2008.…”
Section: Governmentmentioning
confidence: 99%